Sustainability Comparison Between Organic and Conventional Systems at Farm and Field Scale: A Case Study in Olive Production Systems in Apulia Region - Calabrese, Jenny; Pacini, Cesare; Vazzana, Concetta; Nikolla, Mariana (European Journal of Sustainable Development, 2013)
Dependence of conventional agricultural systems on chemical fertilizers and pesticidesmakes agricultural systems less stable and important drift polluters influencing to theregional and global sustainability. This problem made human being think about thealternative systems: agricultural systems that mimic natural systems and are friendly to theenvironment; those have higher economical efficiency concerning production level andcosts. The objective of the present study was sustainability assessment and comparison oforganic and conventional system with special focus environmental and economicalperformance. The case study consisted of two organic and conventional olive producingfarms in the South of Italy. The method used for sustainability assessment wasEnvironmental Accounting Information System (EAIS) that integrates togetherenvironmental (soil organic matter, soil erosion, genetic and landscape biodiversity,EPRIP, etc ) and economical indicators (gross margin). Data used for assessment ofEAIS indicators values were mainly collected from: farm economic-accounting systems,interviews, farm maps, area public organizations, bibliographical sources, farm nutrientaccounting systems, observations and field assessments and chemical soil analyses. Theindicator values measured into two farms were compared to theoretical or referenceindicator values. Based on indicator assessment it was concluded that organic olivegrowing farm had better performance than conventional farm.